1994
DOI: 10.1021/ma00101a010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PMDA-ODA Polyimide Films by External Reflectance Infrared Spectroscopy

Abstract: Reflectance infrared spectroscopy has been carried out for quantitative structural analysis of polyimide films thinner than lo00 A. Reflection spectra have been simulated for isotropic polyimide films of specific thickness on a metallic substrate. Structural analysis was based on a number of infrared active vibrations particularly sensitive to changes in chain conformation or packing. The structure of these films was compared with that obtained by annealing experiments on free standing films and crystalline po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…This indicates that the orientation distribution of imide rings is almost isotropic around the chain axis, and it is independent of the molecular structures and the film sides. This result is consistent with previous studies22, 27 which reported that the imide planes are oriented parallel to the film surfaces only for very thin films.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This indicates that the orientation distribution of imide rings is almost isotropic around the chain axis, and it is independent of the molecular structures and the film sides. This result is consistent with previous studies22, 27 which reported that the imide planes are oriented parallel to the film surfaces only for very thin films.…”
Section: Resultssupporting
confidence: 94%
“…PIs can be easily processed into thin films by casting or spin‐coating of solutions of PIs or their precursors, that is poly(amic acid) (PAA) or poly(amic acid esters). There have been a number of studies for investigating chain orientation and anisotropy in their properties such as coefficient of thermal expansion11–13 (CTE), elastic modulus,11, 12 and refractive index 14–33. The magnitude of anisotropies in these properties basically depends on two factors: the intrinsic anisotropy and the degree of orientation of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…All PI films prepared in this study exhibit good transparency in the visible region, and no scattering of light was observed. Although some rigid‐structured PIs exhibit semi‐crystalline nature,7, 8, 14, 25–28 no peaks related to crystalline components are observed in the WAXD patterns for the present PI films as shown in Figure 2. The shoulder peaks observed around 2Θ = 20° are assigned to amorphous halos.…”
Section: Resultsmentioning
confidence: 73%
“…On the other hand, the degree of chain orientation is directly related to the anisotropies in optical, dielectric, and mechanical properties of polymers. The degree of PI chain orientation have been studied using various methods such as birefringence measurements (Δ n ),9–12 polarized Fourier transform infrared (FTIR) spectroscopy,13–16 and dichloic ratios in absorption spectra using doped dyes 11, 17. In particular, Δ n has been widely used as the concise estimation of chain orientation because it is easily and precisely evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…96͔͒ and the silicon-diode temperature sensor was attached onto the upper surface of the specimen to monitor the specimen temperature. [97][98][99][100][101][102] The LF method was executed by using T-7000 ͑ULVAC-Riko͒. 77 The ruby laser power was 6 J/pulse, the laser spot radius was 10 mm, and the decay filter was inserted to minimize the temperature increase on the front surface.…”
Section: Methodsmentioning
confidence: 99%